Frataxin is essential for zebrafish embryogenesis and pronephros formation - Wesley S. Ercanbrack; Austin Dungan; Ella Gaul; Mateo Ramirez; Alexander J. DelVecchio; Calvin Grass; Rebecca A. Wingert (Frontiers in Cell and Developmental Biology)
Background and objectivesFriedreich’s Ataxia (FRDA) is a genetic disease that affects a variety of different tissues. The disease is caused by a mutation in the frataxin gene (FXN) which is important for the synthesis of iron-sulfur clusters. The primary pathologies of FRDA are loss of motor control and cardiomyopathy. These occur due to the accumulation of reactive oxygen species (ROS) in the brain and the heart due to their high metabolic rates. Our research aims to understand how developmental processes and the kidney are impacted by a deficiency of FXN.MethodsWe utilized an antisense oligomer, or morpholino, to knockdown the frataxin gene (fxn) in zebrafish embryos. Knockdown was confirmed via RT-PCR, gel electrophoresis, and Sanger sequencing. To investigate phenotypes, we utilized several staining techniques including whole mount in situ hybridization, Alcian blue, and acridine orange, as well as dextran-FITC clearance assays.Resultsfxn deficient animals displayed otolith malformations, edema, and reduced survival. Alcian blue staining revealed craniofacial defects in fxn deficient animals, and gene expression studies showed that the pronephros, or embryonic kidney, had several morphological defects. We investigated the function of the pronephros through clearance assays and found that the renal function is disrupted in fxn deficient animals in addition to proximal tubule endocytosis. Utilizing acridine orange staining, we found that cell death is a partial contributor to these phenotypes.Discussion and conclusionThis work provides new insights about how fxn deficiency impacts development and kidney morphogenesis. Additionally, this work establishes an additional model system to study FRDA.